Effect of Interest in Mathematics Learning on Students’ Performance - Wahid, Sharifah Norhuda Syed; Yusof, Yusharina; Wahid, Nurmarni Athirah Abdul (Randwick International of Education and Linguistics Science Journal, 2025)
The purpose of this study is to investigate how interest influences mathematics learning among science students in higher education. Interest plays a significant role, acts as a powerful motivator to influence student's positive attitude and actively encouraging their effort in understanding mathematics. Exploratory factor analysis, confirmatory factor analysis and structural equation modeling methods used to analyse the data collected from 239 selected students. The results proved that the interest significantly has a positive effect to greater success in mathematics (p-value = 0.000). This study reveals that more than 15 points will be achieved for an additional level of interest and indirectly promoting higher education students to have better motivation level towards mathematics. Therefore, to maximize positive interest, enhanced understanding, and a more engaged learning experience in mathematics, it is suggested that a great effort be made to create a supportive and positive learning environment.